1999
DOI: 10.1159/000018689
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Leiomyosarcoma

Abstract: Malignant stromal tumours of the duodenum are rare. The efficacy of surgical resection for duodenal leiomyosarcoma was assessed in 5 patients treated over an 11-year period, probably the largest series treated by a single surgeon. There were 3 women and 2 men with an age range of 27–52 years. Tumours were large (8.5–21 cm diameter) and partly cystic (4 cases). They arose from the second (2), third (2) and fourth parts of the duodenum. Resection was a major undertaking and comprised either partial duodenectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…35 It is generally agreed that the treatment of choice is surgical removal of the mass. 1,[36][37][38] Local resection is appropriate when feasible, but wide resection can be justified as invasion of adjacent organs does not preclude a cure. Duodenal GISTs have a mean survival of 50 months 35 and a 5-year survival of almost 50%.…”
Section: Discussionmentioning
confidence: 99%
“…35 It is generally agreed that the treatment of choice is surgical removal of the mass. 1,[36][37][38] Local resection is appropriate when feasible, but wide resection can be justified as invasion of adjacent organs does not preclude a cure. Duodenal GISTs have a mean survival of 50 months 35 and a 5-year survival of almost 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Pourtant, 50 % des carcinomes du grêle siègent dans le duodénum ; les lymphomes et les sarcomes sont par contre rares dans le duodé-num, et la plupart sont répartis sur le jéjunum et l'iléon [4]. Seulement 15 à 28 % des léiomyosarcome de l'intestin grêle se situent sur le duodénum et représentent 10 % des tumeurs duodénales malignes [5]. Le léiomyosarcome duodénal atteint plus fréquemment les hommes que les femmes [4].…”
Section: Discussionunclassified
“…Indeed, on one hand the anatomical complexity of the duodenum imposes different procedures adapted to the location of the tumor, and on the other hand, the rarity of lymph node metastases arouses debate for the need for node dissection. Among the published cases, only 52 cases had a curative surgery [2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The review of the various procedures carried out (Table 1) found that the choice of surgical procedure depended much more on the location and the size of the tumor that on the need for node dissection.…”
Section: (B)mentioning
confidence: 99%
“…To achieve this, the resection should remove when possible all the adjacent invaded organs [6,8]. As for our second patient, the survival becomes compromised if the resection margins are invaded [9].…”
Section: (B)mentioning
confidence: 99%